Role of Tim4 in the regulation of ABCA1+ adipose tissue macrophages and post-prandial cholesterol levels - M. S. Magalhaes (Nature Portfolio, 2021)
Diverse macrophage subsets are found in adipose tissue where they regulate its physiology. Here, the authors used single-cell RNA sequencing to analyse the effect of post-prandial lipids on adipose tissue macrophages and identify Tim4 as a regulator of ABCA1+ macrophage function and post-prandial cholesterol transport.